2009
DOI: 10.1007/s00330-009-1587-z
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of dual-source computed tomography in quantitative assessment of low density coronary stenosis—a motion phantom study

Abstract: DSCT enables highly reproducible quantification of low density stenosis, but underestimates the degree of stenosis, especially in small vessels. Area-based measurements reflect the true degree of stenosis with higher accuracy than diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…3). This finding is in consistence with previous studies and consensus clinical perception in CCTA [15][16][17]. As recommended by the reference protocol guide, to minimize artifacts due to cardiac motion for heart rates above 75 bpm, protocol C should be employed [12].…”
Section: Discussionsupporting
confidence: 83%
“…3). This finding is in consistence with previous studies and consensus clinical perception in CCTA [15][16][17]. As recommended by the reference protocol guide, to minimize artifacts due to cardiac motion for heart rates above 75 bpm, protocol C should be employed [12].…”
Section: Discussionsupporting
confidence: 83%
“…The main limitation of this study in the inclusion of noncomplex, non-calcified lesion in which coronary CTA has proven to have higher accuracy; therefore, this finding should be confirmed in a more complex population [22]. Also, the low incidence of in-scaffold restenosis limits the conclusion of this analysis to patent scaffolds.…”
Section: Limitationsmentioning
confidence: 88%
“…However, ISR has become an increasingly serious complication and has consequently become a focus of intervention therapy. 13,14 ISR Assessment by DSCT in Patients with Atrial Fibrillation: Presently, both foreign and domestic studies of the evaluation of coronary ISR with DSCT are more focused on patients with regular rhythms. Compared with fluoroscopy, CT has been shown to be markedly more sensitive for detecting gaps between multiple stents (16.9 vs. 1.0%), which have been shown to be associated with ISR.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, our study showed no need for drugs to control heart rate and demonstrated that DSCT could obtain satisfactory imaging quality for coronary examination purposes; this was consistent with the findings of other studies. 13,14 ISR Assessment by DSCT in Patients with Atrial Fibrillation: Presently, both foreign and domestic studies of the evaluation of coronary ISR with DSCT are more focused on patients with regular rhythms. Because of heart rate fluctuations and variability in patients with arrhythmia, artifacts would easily be generated.…”
Section: Discussionmentioning
confidence: 99%